IMPROVING STUDENTS’ READING COMPREHENSION BY USING MIND MAPPING TO THE SECOND SEMESTER STUDENTS OF MANAJEMEN INFORMATIKA DEPARTMENT OF STMIK MATARAM - PATHULA INDRIAN; SOPIAN SAORI (GANEC SWARA, 2018)
The aims of the study was to improve the students’ reading comprehension in learning English especially reading. This research belongs to action research. Based on the observations, the problems found in teaching reading comprehension were text difficulty and ineffective instruction. The study consisted of two cycles. The data were obtained by interviewing the students of the second semester of Manajemen Informatika at Sekolah Tinggi Manajemen Informatika Komputer (STMIK) Mataram, holding the discussion with the lecturer, and the collaborator, and doing observations in the English teaching and learning process. The instruments of the study were a pre-test and post-test, observation guidelines, and interview guidelines. Qualitative and quantitative methods were used to collect the data. The data were analyzed from the field notes, interview transcript and the result of the pre-test and post-test.The result of the study showed that the students’ reading comprehension in English teaching and learning process improved through mind mapping. The result of the research showed that the mean score of post-test was higher than that of the mean score of the pre-test. The mean score of pre-test was (62.78) and the mean score of post-test was (75. 89). Thus, there was an increasing point of 13. 11